Peran Komite Audit Dalam Good Corporate Governance - Lidia Tambunan; Bonifasius H. Tambunan (Jurnal Riset Akuntansi dan Bisnis, 2021)
Overall corporate governance relating to the system and discussion of discussions on the company. The agent has a behavior that tends to side with the stakeholders as a principal that benefits the company. If more and more stakeholders are harmed, the company's reputation will become worse and no one will cooperate with the company. The role of the audit committee on the principle of equality is an important role for parties who are in line with the company so that it is fair to all companies so that no one is harmed. The role of the audit committee is based on the principle of responsibility, which plays an important role in running a good / healthy business, not in its own interests.